Electrokinetic nanoparticle transport in an interconnected porous environment: Decoupling cavity escape and directional bias - Anni Shi; Siamak Mirfendereski; Ankur Gupta; Daniel K. Schwartz (Proceedings of the National Academy of Sciences, 2025)
Electrokinetic transport of nanoparticles in porous media is crucial for separation technologies, but the boundary-field coupling effects in three-dimensional (3D) interconnected porous spaces remain challenging to understand. Using superresolution 3D tracking of nanoparticles in interconnected cavities, we observed an unexpected disconnect between cavity escape time and directional bias as a function of electric field strength. The cavity escape times of individual nanoparticles decreased dramatically even with weak fields (2 V/cm), enhancing effective diffusion. However, directional bias was negligible at low field strengths, and became significant only for stronger fields (~7 V/cm). Simulations revealed that at low field strengths, when Brownian motion dominated the nanoparticle dynamics [Péclet number (Pe) < 0.005], the transport was stochastic with accelerated random exploration and cavity escape without directional preference, facilitated by the coordination of weak electrophoresis and electroosmotic (EO) recirculating flow. The combined effect creates localized vortices that position particles closer to internal boundaries, increasing exit encounter probability. At larger Pe values, electrophoretic forces start to overcome the apparently random motion, and establish a preferred migration direction through the porous network. These findings demonstrate the delicate balance between Brownian fluctuations, electrophoretic force, and EO flow in interface-confined and interconnected environments, providing mechanistic insights for optimizing electrokinetic separation in chromatographic columns, separation membranes, and nanocargo delivery systems.